The Role of Forum Silaturahim Studi Ekonomi Islam (FoSSEI) in Increasing Public Awareness and Understanding of Islamic Economy in West Java Province - Siti Zuhroh; Olivia H. Munayang; Fadila Almahdali; Nunung Apriani (Westscience Press, 2023)
Islamic economics has become a topic of increasing interest from the Indonesian public and government in recent years. West Java Province as one of the centers of national economic development is also not left behind in developing the Islamic economy. In order to improve public knowledge of Islamic economics, FoSSEI, an organization made up of students and students interested in Islamic economics, plays a crucial role. The purpose of this study is to ascertain how the FoSSEI contributes to greater public knowledge and comprehension of Islamic economics in the West Java Province. A qualitative descriptive research methodology was adopted, and data were gathered through interviews with FoSSEI members, scholars, and practitioners of Islamic economics, as well as communities participating in FoSSEI operations. In West Java Province, the findings indicated that FoSSEI plays a significant role in raising public knowledge of and comprehension of Islamic economics. FoSSEI has successfully held various activities such as seminars, training, and community service programs that focus on developing the Islamic economy. These activities have succeeded in increasing public understanding and awareness of Islamic economics.